Adaptive Streetscape Architecture of Local Business Neighborhood in Jalan Jendral Urip Sumoharjo - Herlian, Erwin; Aji, Fauzi Mizan Prabowo (Universitas Muhammadiyah Surakarta, 2024)
Jalan Jendral Urip Sumoharjo in Surakarta is an example of a street in a big city in Indonesia that has adapted in terms of its streetscape architecture. This adaptation is influenced by many factors and possibilities that need to be explored in the future. One of the dominant determining factors is the discovery of facts about local business development in carrying out trading activities on this road section. This research explores forms of streetscape architectural adaptation in the context of the local business environment, with a focus on Jalan Jendral Urip Sumoharjo. The study explored the unique characteristics of the streetscape, emphasizing its role in responding to a dynamic local business community. The adaptive nature of streetscape architecture is observed by considering factors such as design, functionality, and its integration with local businesses. Jalan Jendral Urip Sumoharjo serves as a specific case study, showcasing the intersection between adaptive urban design and the vitality of the local business environment. Adaptation to the streetscape in terms of architecture is influenced by user needs, in this case the majority of traders who need flexibility.